2014
DOI: 10.1111/jsr.12174
|View full text |Cite
|
Sign up to set email alerts
|

Examining the effects of sleep delay on depressed males and females and healthy controls

Abstract: SUMMARYIndividuals with major depressive disorder typically exhibit sleep electroencephalograpy abnormalities which have been shown to vary by sex. Recent research has shown that depressed males display deficits in slow wave sleep and delta electroencephalograph (EEG) activity that are not apparent in depressed females. This may suggest that males and females with depression vary with respect to their homeostatic regulation of sleep. Utilizing archival data, the present study examined the effects of a 3-h slee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…These results also lend preliminary support for the hypothesis that suicide risk is associated with reduced delta activity beyond the decrease in delta activity typical of depression (Armitage, 1995; Armitage et al, 2000a, 2000b; Cheng et al, 2015; Goldschmied et al, 2014; Kupfer et al, 1986; Lotrich and Germain, 2015). Although no differences were observed for absolute whole night delta activity, relative delta activity was reduced in participants with high suicidal ideation and MDD, controlling for depression symptoms.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…These results also lend preliminary support for the hypothesis that suicide risk is associated with reduced delta activity beyond the decrease in delta activity typical of depression (Armitage, 1995; Armitage et al, 2000a, 2000b; Cheng et al, 2015; Goldschmied et al, 2014; Kupfer et al, 1986; Lotrich and Germain, 2015). Although no differences were observed for absolute whole night delta activity, relative delta activity was reduced in participants with high suicidal ideation and MDD, controlling for depression symptoms.…”
Section: Discussionsupporting
confidence: 67%
“…Sleep electroencephalography (EEG) has been identified as a tool to identify potential biomarkers for disorders closely related to suicide such as major depressive disorder (Armitage et al, 2006; Benca et al, 1992; Cheng et al, 2015; Goldschmied et al, 2014; Steiger and Kimura, 2010). Further, findings from a meta-analysis indicate that sleep EEG abnormalities may also represent a transdiagnostic psychophysiological mechanism that cuts across disorders (Baglioni et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Delta power was averaged across all electrode sites from all the non-REM periods. Details regarding the quantification of delta activity has been previously described (see Goldschmied et al, 2014).…”
Section: Data Collection and Processingmentioning
confidence: 99%
“…While several studies have indicated that abnormalities in slow-wave sleep are characteristic of those with depression (Beersma and Van den Hoofdakker, 1992;Armitage and Hoffmann, 2001;Goldschmied et al, 2014), the specific relationship between slow-wave abnormalities and the various dimensions in the phenomenology of depression is still unclear. Conceptualizing and understanding depression utilizing a dimensional approach is increasingly important due to the heterogeneity in symptom presentation between individuals.…”
Section: Introductionmentioning
confidence: 97%